CULTURAL INFLUENCES AND BEAUTY CONSTRUCTS: AN ANALYSIS OF TONI MORRISON'S "THE BLUEST EYE" - Asim Ismail, Islam; Bsharat, Tahani; Mohapatra, Yogasmita (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
This article analyses how The Bluest Eye, Toni Morrison's earliest novel, presents beauty ideals, identity formation, and societal transformation. Drawing on Morrison's representation of the tragic protagonist Pecola Breedlove, the analysis explores how dominant white standards of beauty become embedded within black culture, leading to destructive internalized racism and self-hatred. It discusses Morrison's skillful storytelling techniques for highlighting the tragic gap between Pecola's actual black female identity and her unattainable white feminine ideal. Additionally, the paper demonstrates how Morrison utilizes Pecola's story to astutely critique the influential role of culture in shaping beauty ideals that engender self-loathing and fractured identities in 1940s America. Further, it outlines how textbooks, family backgrounds, and communities significantly shape what is considered beautiful. The authors argued that Morrison's novel is like an insightful mirror that reflects how cultural beliefs about beauty find their way into societies. This paper also argues for the urgent need to challenge pervasive racism and bias, engender deep self-loathing and fractured identities in young black girls, and advocate for more inclusive standards of beauty and self-worth. The authors believe that nearly fifty years after its publication, Morrison’s brilliant literature remains vital to ongoing efforts toward inclusion, empowerment, and social transformation.